Multifunctional Nanotechnology-Enabled Sensors for Rapid Capture and Detection of Pathogens - Fatima Mustafa; Rabeay Y. A. Hassan; Silvana Andreescu (Sensors, 2017)
Nanomaterial-based sensing approaches that incorporate different types of nanoparticles (NPs) and nanostructures in conjunction with natural or synthetic receptors as molecular recognition elements provide opportunities for the design of sensitive and selective assays for rapid detection of contaminants. This review summarizes recent advancements over the past ten years in the development of nanotechnology-enabled sensors and systems for capture and detection of pathogens. The most common types of nanostructures and NPs, their modification with receptor molecules and integration to produce viable sensing systems with biorecognition, amplification and signal readout are discussed. Examples of all-in-one systems that combine multifunctional properties for capture, separation, inactivation and detection are also provided. Current trends in the development of low-cost instrumentation for rapid assessment of food contamination are discussed as well as challenges for practical implementation and directions for future research.